THE PHENOMENON OF HUMAN ALIENATION: A SOCIO-POLITICAL ANALYSIS - A. K. Botasheva; F. G. Vagapova; R. N. Vagapov (Современная наука и инновации, 2022)
Alienation in the modern world has become a sign not only of the ill-being of a single person, but, unfortunately, of society, which generates in the subject an irreconcilable conflict with the outside world, complete rejection of the outside world, its foundations, canons and rules. Alienation has become a denial of possible cooperation, co-creation, lack of empathy, etc. The article proves that the phenomenon of alienation is not only a psychological or social phenomenon concerning the discrepancy between the individual's expectations and social reality. The problem of alienation becomes a problem of society, which suffers from "shooters" and terrorists, gives uncertainty to society in state protection, equality of all before the law, confusion appears before the unknown, communication links are disrupted, a sense of insecurity before criminals appears in society, etc. The authors suggest ways to minimize the processes of alienation in modern society.